Life Cycle Assessment of Heavy Equipment Repair and Hazardous Waste Storage: Environmental Optimization at a Coal Mining Contractor - Anggito Setya Ichsan; Nur Iswanto; Nugroho Dewayanto; Margono Margono; Osaegi Restu Amrullah (Universitas Darussalam Gontor, 2025)
This study applies Life Cycle Assessment (LCA) with Cradle-to-Gate approach to optimize environmental management at PT PPA, a coal mining contractor generating substantial hazardous waste (B3) from continuous heavy equipment maintenance. Operational data from January-April 2025 documented 136.94 tons of solid waste (contaminated rags, filters, hoses, batteries, sludge) and 634.07 tons of liquid waste (used lubricants and chemicals). System boundaries spanned maintenance activities through waste storage at the licensed Temporary Storage Facility (TPS). Environmental impact assessment quantified five key categories: (1) Global Warming Potential: 44.3 tons CO₂e/month, dominated by generator diesel consumption (35.9 tons CO₂e/month); (2) VOC emissions:374 kg/month, primarily from contaminated rags (67% contribution); (3) Photochemical Ozone Creation Potential: 602.5 kg C₂H₄-eq/month; (4) Particulate Matter Formation Potential: 13.92 kg PM10-eq/month; and (5) Ecotoxicity from heavy metals (Cd, Pb, Mn), hydrocarbons, and cleaning chemicals. Benchmarking against Indonesian regulations (PP 101/2014, PP 22/2021) and international mining studies confirmed low-to-moderate impact classification, though specific hotspots warrant attention. Strategic mitigation recommendations include implementing closed storage systems (40-50% VOC reduction potential), energy efficiency upgrades (15-20% GHG reduction), waste minimization programs, and lubricant recycling. These interventions support Environmental, Social, and Governance (ESG) principles and advance Sustainable Development Goals (SDGs 12.4, 13.2, 3.9) implementation, positioning PT PPA as a sustainability leader in Indonesia's mining sector.